Effects of an intervention focused on parental socialization practices on internalizing problems in childhood (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
This study evaluated the efficacy of an intervention focused on socialization practices with 13 mothers and one father of children between three and six years with internalizing profile, divided into two groups: intervention and comparison. The CBCL/1½-5 years and CBCL/6-18 years were used for assess internalizing problems, indicating only a significant reduction in somatic complaints in the intervention group from pre to post-test. This reduction may be associated with the following factors: (a) increase of the predictability of contingencies parent-child relationship, decreasing its aversive character and leading to respondent extinction of physiological responses that are related to somatic complaints and (b) replacement of overprotective and coercive practices by facilitating socioemotional development leading to the extinc-tion of respondent physiological responses related to emotions elicited by coercive practices and overprotection. The limitations of intervention and methodological aspects common in studies conducted in clinical settings are discussed.
Keywords: internalizing problems; parental socialization practices; group intervention; infancy; quasi-experimen-tal design